A települések belső szerkezetének vizsgálata a lakosság térbeli eloszlása alapján - Kocsis, Zsolt (Tér és Társadalom, 1996)
The study started from the concept that the place of residence, the residential environment shape and influence people who, in return, can also transform their residential environment. It is not indifferent in the life of a seftlement whether its population is endowed or not with the skills and possibilities which enable transitions of a positive direction. In other cases, because of their income level, social position, age etc., they cannot help bringing their residential environment towards deterioration, running down infrastructuré and buildings, thus worsening, further worsening the judgement and prestige of certain parts of the towns and this way also of those who live there. It is also decisive if a town can provide or not areas offering acceptable conditions for social activities, work, recreation etc. If not, the active, socially and fmancially mobile citizens will leave the town. Among other things, that is why researches on the spatial characteristics of population are important: The social spatial structure of the individual settlements, supplemented with housing indices, are very good indicators of the present situation and opportunities of certain parts of the towns. Knowing the rearrangement processes in the inner space of the settlements, intervention may come in time in order to save some blocks from deterioration and give some handicapped social layers a last chance by creating a better residential environment. Half of the concept is of rather sociological nature: The place occupied in the urban space partly reflects, partly causes and partly is the result of the social position. Its population-transforming effects indirectly work, as in the uniform block of flats the occupational and age structure of the population became much more homogeneous by 1990 than it was in 1980. As the panel flats offer little versatility, their population partly becomes apathetic, partly is exchanged and those move in who have to make do with the existing conditions. The other half is much better supported by data: Human beings transform their residential environment, the space in which they live.